PROCESS RISK MANAGEMENT FOR BREAD PRODUCT DELIVERY OF MAKASSAR TO MANADO ROUTE AT PT. XYZ - Faisal Angriawan Malik; Syarifuddin M. Parenreng; Sapta Asmal (SEAN Institute, 2023)
Community service aims to increase the knowledge and understanding of citizens to reduce the risk of non-communicable diseasesers. This is due to success in product delivery will affect customer service and satisfaction which are an important part of the product marketing strategy. Therefore, risk identification in the process flow product delivery is an important thing to do in order to minimize the risks that occur which can hinder the success of product delivery. Risk identification in this study was carried out using a brainstorming approach, namely identifying every possible activity that may cause unwanted risks and involving several PT experts. X. The results from the brainstorming approach showed that there are 13 risk agents and 18 risk events. Then, a fuzzy logic approach was carried out to be able to determine an assessment of the occurrence of the risk agent and the severity of the risk event. Also, the House of Risk (HOR) approach was carried out to analyze the level of impact severity of risk and find out the sequence of risks that first get treatment and to map the probability impact matrix. From the results of this study, the researchers obtained five aspects that need to be improved, namely aspects of HR, Systems, Leadership, Relations and Environment. From these five aspects, 15 mitigation actions to help companies minimize any risks that occur were produced.